The Impact of an Auditor’s Professional Commitment to The Whistleblowing Intention: Locus of Control as a Moderating Variable - YANI JALIL, FITRI (The Indonesian Journal of Accounting Research, 2013)
This study examines the antecedent of the whistleblowing intentionwith the auditor’s professional commitment. This study was modifiedby using a sample of real auditors, whereas previous research usedaccounting students. This study also submits the locus of control as amoderating effect on the relationship. This study focuses on a reexaminationof the extent the whistleblowing intention issue is tested by professionalcommitment and the locus of control as moderating effects.The data were obtained from 105 junior and senior external auditorsfrom public accounting firms in Jakarta. The result indicates that thereis no significant impact by professional commitment or the moderatingeffect of the locus of control on the whistleblowing intention. It meansthat the professional commitment and locus of control can’t increase thewhistleblowing intention of a real auditor and that other factors becomethe barrier to whistleblowing.